Expression Levels of Sperm Genes Associated with Energy Production Pathways Regulate Fertility Status of Bulls - Ramya, Laxman; Swathi, Divakar; Archana, Santhanahalli Siddalingappa; Arangasamy, Arunachalam; Binsila, B Krishnan; Krishnappa, Balaganur; Selvaraju, Sellappan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Sperm biomolecules impact the reproductive success of a bull in many ways from fertilization to the health of the offspring. The  energy produced within the sperm enables them to remain motile and allows them to participate in fertilization events. In this study,  we deciphered the genes associated with energy production and their influence on the fertility rate. Post-thaw buffalo semen samples  (n=21) were analysed for sperm kinematics and field fertility for selecting high (n=5) and low (n=5) fertile samples. Sperm total RNAs  were extracted using a double lysis method followed by column-based extraction and sequenced using the Illumina platform. The  expression levels of the genes involved in energy-regulating pathways were analyzed. Among these genes, 14.6% were significantly  (p0.5) with progressive motility and velocities. In these, up-regulated  genes were involved in chemokine signaling (ADCY2 and JAK2, p=0.0001), calcium signaling (AGTR1 and SLC25A4,p=0.0002) and oocyte  meiosis (ADCY2 and ADCY3, p=0.049). The increase in the expression of ATP-producing genes substantiates the improved progressive  motility (64.51±5.79 vs 33.07±3.34 %), curvilinear velocity (70.58±4.32 vs 50.15±4.92 μm/sec), straight-line velocity (39.84±3.16 vs  26.02±2.52 μm/sec) and average path velocity (49.46±3.59 vs 32.99±3.45 μm/sec) in high fertile bulls compared to low fertile bulls. The  study suggests that the expression level of differentially expressed genes associated with energy-regulating pathways influences the  fertilizing ability of sperm.
Keywords: Bull fertility; Energy-production; Fertilization; Sperm kinematics; Sperm transcriptome